2019
DOI: 10.1108/imds-01-2018-0009
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and use predictors of fitness wearable technology and intention to recommend

Abstract: Purpose The purpose of this paper is to identify the key facilitators and inhibitors of fitness wearable technology (FWT) adoption and the intention to recommend this technology. Design/methodology/approach An innovative and integrated research model was developed by combining constructs from two well-established theoretical models, the extended unified theory of acceptance and use of technology (UTAUT2) and diffusion of innovation (DOI). The proposed research model was empirically validated using data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
170
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 165 publications
(228 citation statements)
references
References 66 publications
22
170
1
6
Order By: Relevance
“…Price and value is a cost/benefit analysis consumers analyze to determine if they want to use a given technology (Venkatesh et al, ). However, our results were consistent with the findings of other studies related to wearable devices (Talukder et al, ), as both have shown that price or value has no significant effect on intention to use technology. For this study, we predicted that if individuals were required to spend a significant amount of money for the service, they might be reluctant to use WTDs.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Price and value is a cost/benefit analysis consumers analyze to determine if they want to use a given technology (Venkatesh et al, ). However, our results were consistent with the findings of other studies related to wearable devices (Talukder et al, ), as both have shown that price or value has no significant effect on intention to use technology. For this study, we predicted that if individuals were required to spend a significant amount of money for the service, they might be reluctant to use WTDs.…”
Section: Discussionsupporting
confidence: 93%
“…However, both of the studies utilized IT professionals, whose use of the technology was not voluntary. Talukder, Chiong, Bao, and Hayat Malik (2019) use UTAUT2 to examine the adoption of smartwatches. In the past, researchers have identified key facilitators and inhibitors of fitness-wearable technology adoption as well as intention to recommend the technology.…”
Section: Mots Clésmentioning
confidence: 99%
See 3 more Smart Citations